Minat Mahasiswa STAIN Jember Mengikuti Pembelajaran Komputer melalui Pusdikom: The Interest of Students at the State Islamic College (STAIN) Jember in Participating in Computer Learning through Pusdikom - Abdul Rahim (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2005)
The rapid development of computer technology has made it a compulsory subject at STAIN Jember, managed by Pusdikom, yet the level of student interest remains empirically unmeasured. This study aims to determine student interest in terms of competence, course requirements, and recreational aspects. A descriptive survey was conducted with 60 students from various study programs, using questionnaires and interviews. The results showed that 70% of respondents participated in computer learning because it meets their needs, particularly for completing academic assignments; 26.7% followed the course merely to fulfill credit requirements, as it is compulsory; and 3.3% participated just to spend free time. In conclusion, most students are motivated by the relevance of computers to academic needs, though facility improvements and a better student-lecturer ratio are necessary. It is recommended that infrastructure be enhanced and need-based curricula be optimized. Pesatnya perkembangan teknologi komputer menjadikannya mata kuliah wajib di STAIN Jember yang dikelola melalui Pusdikom, namun belum diketahui secara empiris tingkat minat mahasiswa. Penelitian ini bertujuan mengidentifikasi minat mahasiswa ditinjau dari aspek kompetensi, tuntutan mata kuliah, dan kesenangan. Metode yang digunakan adalah survei deskriptif dengan sampel 60 mahasiswa dari berbagai program studi, menggunakan angket dan wawancara. Hasil penelitian menunjukkan 70% responden menyatakan mengikuti pembelajaran komputer karena memenuhi kebutuhan, terutama membantu menyelesaikan tugas perkuliahan; 26,7% mengikuti hanya untuk memenuhi jumlah SKS karena sifatnya wajib; dan 3,3% mengikuti sekadar mengisi waktu luang. Kesimpulannya, mayoritas mahasiswa berminat karena relevansi komputer terhadap kebutuhan akademik, namun perlu peningkatan fasilitas dan rasio dosen-mahasiswa. Direkomendasikan penambahan sarana prasarana dan optimalisasi kurikulum berbasis kebutuhan.